Residential air quality near noise barriers strongly affected by wind velocity - Ali Kooh Andaz; Xiaoyu Li; Ville Silvonen; Jarkko V. Niemi; Juan Andrés Casquero-Vera; Sami D. Harni; Leena Järvi; Topi Rönkkö; Anu Kousa; Tommy Chan; Tuukka Petäjä; Hilkka Timonen; et al. (Science of The Total Environment, 2025)

How air cleaners, ventilation, and outdoor air pollution influence air quality in European hospitals: Case studies from Finland and Romania - Mohamed Elsayed; Ville Silvonen; Anni Luoto; Henna Lintusaari; Jani Hakala; Hilkka Timonen; Sami D. Harni; Topi Rönkkö; Piia Sormunen (Building and Environment, 2025)

Long-term characterization of organic and elemental carbon at three different background areas in northern Europe - Milla Friman; Minna Aurela; Karri Saarnio; Kimmo Teinilä; Jutta Kesti; Sami D. Harni; Sanna Saarikoski; Antti Hyvärinen; Hilkka Timonen (Atmospheric Environment, 2023)

Cross-continental differences in Black-tailed Godwit breeding densities are best explained by arthropod abundance in the chick-hatching period - Miguel Silva-Monteiro; Hannes Pehlak; Sami Timonen; Jorma Pessa; Esko Pasanen; Mo Verhoeven; A. H. Jelle Loonstra; Theunis Piersma; Frederic Robin; Michał Korniluk; Melissa Onwezen; Morten Bongers; et al. (Journal of Ornithology, 2023)

Effects of emission sources on the particle number size distribution of ambient air in the residential area - Sami D. Harni; Sanna Saarikoski; Joel Kuula; Aku Helin; Minna Aurela; Jarkko V. Niemi; Anu Kousa; Topi Rönkkö; Hilkka Timonen (Atmospheric Environment, 2023)

Cold weather increases winter site fidelity in a group-living passerine - Veli-Matti Pakanen; Juhani Karvonen; Jaana Mäkelä; Jukka-Pekka Hietaniemi; Tuomo Jaakkonen; Elina Kaisanlahti; Miila Kauppinen; Kari Koivula; Aappo Luukkonen; Seppo Rytkönen; Sami Timonen; Jere Tolvanen; et al. (Journal of Ornithology, 2018)

Global population collapse in a superabundant migratory bird and illegal trapping in China - Johannes Kamp; Steffen Oppel; Alexandr A. Ananin; Yurii A. Durnev; Sergey N. Gashev; Norbert Hölzel; Alexandr L. Mishchenko; Jorma Pessa; Sergey M. Smirenski; Evgenii G. Strelnikov; Sami Timonen; Kolja Wolanska; et al. (Conservation Biology, 2015)
Persecution and overexploitation by humans are major causes of species extinctions. Rare species, often confined to small geographic ranges, are usually at highest risk, whereas extinctions of superabundant species with very large ranges are rare. The Yellow‐breasted Bunting (Emberiza aureola) used to be one of the most abundant songbirds of the Palearctic, with a very large breeding range stretching from Scandinavia to the Russian Far East. Anecdotal information about rapid population declines across the range caused concern about unsustainable trapping along the species’ migration routes. We conducted a literature review and used long‐term monitoring data from across the species’ range to model population trend and geographical patterns of extinction. The population declined by 84.3–94.7% between 1980 and 2013, and the species’ range contracted by 5000 km. Quantitative evidence from police raids suggested rampant illegal trapping of the species along its East Asian flyway in China. A population model simulating an initial harvest level of 2% of the population, and an annual increase of 0.2% during the monitoring period produced a population trajectory that matched the observed decline. We suggest that trapping strongly contributed to the decline because the consumption of Yellow‐breasted Bunting and other songbirds has increased as a result of economic growth and prosperity in East Asia. The magnitude and speed of the decline is unprecedented among birds with a comparable range size, with the exception of the Passenger Pigeon (Ectopistes migratorius), which went extinct in 1914 due to industrial‐scale hunting. Our results demonstrate the urgent need for an improved monitoring of common and widespread species’ populations, and consumption levels throughout East Asia.

Cerebellar Glucose During Fasting and Acute Hyperglycemia in Nondiabetic Men and in Men with Type 1 Diabetes - Outi Heikkilä; Sari Mäkimattila; Marjut Timonen; Per-Henrik Groop; Sami Heikkinen; Nina Lundbom (The Cerebellum, 2010)

Evidence for abnormal glucose uptake or metabolism in thalamus during acute hyperglycaemia in type 1 diabetes—a 1H MRS study - Outi Heikkilä; Nina Lundbom; Marjut Timonen; Per-Henrik Groop; Sami Heikkinen; Sari Mäkimattila (Metabolic Brain Disease, 2010)

Risk for metabolic syndrome predisposes to alterations in the thalamic metabolism - Outi Heikkilä; Nina Lundbom; Marjut Timonen; Per-Henrik Groop; Sami Heikkinen; Sari Mäkimattila (Metabolic Brain Disease, 2008)